Changes in Levels of Back Pain in Third Trimester of Pregnant Women Who Do Yoga Exercises - Susi Irianti; Sunah Nurjanah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Back pain is a common disorder in pregnancy, pregnant women may have had back pain before. You can do yoga exercises which are useful for forming an upright posture. This research was an experimental one group pretest posttest design. The sample of this study used accidental sampling with a sample of 16 trimester III pregnant women at Masita Clinic. The results of this study showed that the pain scale in the pretest was on a scale of 1 (slight pain) as many as 11 pregnant women (68.75%) and the pain scale in the postest for some of the respondents were on a pain scale of 0 (no pain) as many as 8 pregnant women (50%). Based on the results of the study, it can be concluded that there was a decrease in the level of back pain in third trimester pregnant women after doing yoga.